Update in Laboratory Diagnosis of Thalassemia - Munkongdee, Thongperm; Chen, Ping; Winichagoon, Pranee; Fucharoen, Suthat; Paiboonsukwong, Kittiphong (Frontiers in Molecular Biosciences, 2020)
Alpha-, beta-thalassemias and some abnormal hemoglobins such as hemoglobin E (Hb E) and Hb Constant Spring (Hb CS) are common in Southeast Asia and southern part of China. The complex gene-gene interaction leads to many thalassemic diseases including homozygous β-thalassemia, β-thalassemia/Hb E and Hb Bart’s hydrops fetalis. Laboratory diagnosis of thalassemia requires a number of tests including red blood cell indices, hemoglobin (Hb) and DNA analysis. Thalassemic red cells analysis with an automated hematology analyzer is a primary screening for thalassemia since microcytosis and decreased Hb content of red blood cells is a hallmark of all thalassemic red cells. However, these two red blood cell indices cannot discriminate between thalassemia trait and iron deficiency or between alpha-, beta -thalassemic conditions. Today Hb analysis may be carried out by either automatic high performance liquid chromatography (HPLC) or capillary zone electrophoresis (CE) system. These two systems give both qualitative and quantitative analysis of Hb components and help to do thalassemia prenatal and postnatal diagnosis within short period. Both systems have a good correlation but the interpretation under the CE system should be caution because Hb A2 is clearly separated from Hb E. Especially in case with alpha thalassemia gene interaction, it affects the amount of Hb A2/E. The identification of different thalassemia genotypes can be revealed by the intensities between alpha-/beta-globin chains or alpha-/beta-mRNA ratios. However, none of these techniques can accurately diagnose specific thalassemia genotype. Specific thalassemia mutation can be carried out by DNA analysis. Various molecular techniques have been used for point mutation detection in beta-thalassemia and large-deletion detection in alpha-thalassemia. All of these techniques have some advantages and disadvantages. Recently, screening for both alpha- and beta- thalassemia genes by Next Generation Sequencing (NGS) has been introduced. This technique gives an accurate diagnosis of thalassemia that may be misdiagnose by conventional technique. The major limitation to use NGS for the screening of thalassemia is its cost which is still expensive. All service labs were highly recommend to select the technique(s) they are most familiar and most economic one for their routine use.